MODEL HIBRID MANAJEMEN USAHA PENDIDIKAN INTEGRASI MODAL SPIRITUAL DAN KEBERLANJUTAN EKONOMI DALAM LEMBAGA PENDIDIKAN BERBASIS NILAI - Muhamad Kholil Ridwan; Muhammad Sidiq Purnomo (STKIP Pesisir Selatan, 2026)
Objective: This study aims to develop a hybrid educational business management model that integrates spiritual capital and economic sustainability within a coherent framework. The study addresses the polarization in educational management literature between efficiency-oriented economic approaches and value-oriented normative approaches. Methods: A qualitative library research design was employed through the review and analysis of reputable scientific publications published over the last 10–15 years. Data were collected using documentation techniques and analyzed through thematic analysis to identify patterns, categories, and conceptual gaps concerning spiritual capital and economic sustainability. Results: The findings reveal that spiritual capital functions as a strategic intangible asset that shapes organizational culture, influences managerial decision-making, strengthens stakeholder trust, and supports the long-term sustainability of educational institutions. The literature synthesis produced an integrative model based on the sequence value → culture → strategy → performance, demonstrating that spiritual and economic dimensions are mutually reinforcing rather than contradictory. Novelty: The study proposes a hybrid management model grounded in the Resource-Based View, positioning spiritual capital as a source of competitive advantage and sustainable organizational performance in educational institutions